The Impact of Currency Risk on Non-financial Companies in the UK - Atanassov, Alexandre (2008)
The purpose of this paper is to examine the impacts of currency risk on UK non-financial listed companies from 2001 to 2005. In doing so, this study reveals the existence of a relationship between changes in the stock returns of such companies and fluctuations in the trade-weighted exchange rate of the British pound. This relationship, called exchange rate risk exposure exists at company level. The formation of the mathematical model utilized for this specific empirical research is based on previous studies in the field. The economic conditions during the time-span of the study are also presented. The model itself is similar to the models of Jorion (1990) and Choi and Prasad (1995). It is a two-factor model, which treats stock returns of companies as a linear function of the return on the market and the rate of change in the multilateral exchange rate. Its major goal is to capture the sensitivity of the exchange rate risk factor Ã¢ÂÂ namely, the exposure coefficient. Through the Ordinary Least Squares approach it is determined that 13 out of a total sample of 122 (10.65%) companies display coefficients of exchange rate risk exposure that are statistically significant. 6 out of these 13 or 46% have positive exposure coefficients. It means that depreciation of the UK currency results in a rise in their stock returns. On average, 1% depreciation in the trade-weighed exchange rate of the British Pound results in, ceteris paribus, a rise of 1.795% in firmÃ¢ÂÂs stock return. On the other hand, the remaining 54% (7 out of 13) of firms have negative exposure coefficients. Therefore, they stand to lose from depreciation of the pound (a drop in value by an average of 1.06% for 1% depreciation of the currency). Out of all sectors, only the Real Estate sector participates with more than one member in the group of thirteen firms with statistically significant exposure coefficients. Furthermore, this sector actually displays negative exposure with almost half of the companies from that industry having negative coefficients. In addition to that, in analyzing the impact of currency risk on British non-financial companies, the time period is divided into two 30 month sub-periods. Regarding this sub-level analysis of exposure, during the first 30 months, the exposure of those 13 firms was greater for the majority of them due to the first sub-period exhibiting much greater depreciation in the exchange rate of the pound -3.81% compared to 1.88% depreciation for the whole period. To conclude, future research should be aimed at the determinants of exposure as to what factors contribute to exchange rate risk exposure, because although that has been studied several times, more refinement and new insights are required to elevate our understanding of currency risk sensitivity of companies to a new level.